Parenteral Nutrition in Esophageal Cancer - Voelker, Ricardo; Balboa, Oscar; Lerena, Ana (Cirugía del Uruguay, 1980)
31 cases of patients presenting esophagic cancer, treated by parenteral nutrition are analized. No deaths o·r severe complications due to this proceeding is pointed out. Satisfactory preoperative conditions was reached in sorne patients out of possibilities and anastomotical leak rate was overcomed in 50 % of the patients.